Development of a novel affinity chromatography resin for platform purification of bispecific antibodies with modified protein a binding avidity. (8th March 2018) - Tustian, Andrew D.; Laurin, Linus; Ihre, Henrik; Tran, Travis; Stairs, Robert; Bak, Hanne
Abstract : There is strong interest in the production of bispecific monoclonal antibodies that can simultaneously bind two distinct targets or epitopes to achieve novel mechanisms of action and efficacy. Regeneron's bispecific technology, based upon a standard IgG, consists of a heterodimer of two different heavy chains, and a common light chain. Coexpression of two heavy chains leads to the formation of two parental IgG impurities, the removal of which is facilitated by a dipeptide substitution in the Fc portion of one of the heavy chains that ablates Fc Protein A binding. Therefore, the affinity capture (Protein A) step of the purification process must perform both bulk capture and high resolution of these mAb impurities, a task current commercially available resins are not designed for. Resolution can be further impaired by the ability of Protein A to bind some antibodies in the variable region of the heavy chain (VH ). This article details development of a novel Protein A resin. This resin combines an alkali stable ligand with a base matrix exhibiting excellent mass transfer properties to allow high capacity single step capture and resolution of bispecific antibodies (bsAbs) with high yields. The developed resin, named MabSelect SuRe™ pcc, is implemented in GMP production processes for several bsAbs. © 2018 The Authors Biotechnology Progress published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers Biotechnol. Prog., 34:650–658, 2018